Development of Bekasi History and Culture Learning Model at Elementary School Level - Khoir, Abdul (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to develop a learning model of Bekasi’s Local Subject, history and culture at the elementary school and madrasah ibtida’iyah levels that follow the needs of the community and the Bekasi City government. The research used the Research and Development method with a combination model design of Local Subject Development Procedures with the Instructional Development Model (MPI). The instruments in this study used observation sheets, questionnaires, and tests; then, the existing data was analyzed using descriptive qualitative. The results of expert validation showed that the development of a learning model for local content of Bekasi History and Culture for elementary schools and madrasah ibtidaiyah had fulfilled (valid) procedures scientifically that can be applied in schools and meet the expectations of the people of Bekasi City. The results showed that the effectiveness of the model to Local Subject Development Procedures with the Instructional Development Model (MPI), that was, the average score of student competency test results, was 88.3 above the minimum completeness criterion of 75. The research results could develop student appreciation and creation to support the regeneration process that loved local culture and fosters pride in cultural identity to motivate students to protect and preserve cultural heritage.